The Effects of Patient-Centered Communication on Patient Engagement, Health-Related Quality of Life, Service Quality Perception and Patient Satisfaction in Patients with Cancer: A Cross-Sectional Study in Türkiye - Cuma Çakmak; Özgür Uğurluoğlu (Cancer Control, 2024)
Introduction Patient-centered communication is a type of communication that takes place between the provider and the patient. Objectives It is aimed to reveal the effects of patient-centered communication on patient engagement, health-related quality of life, perception of service quality and patient satisfaction. Method The study was conducted by applying multiple regression analysis to the data obtained from 312 patients with cancer treated in a training and research hospital affiliated to the Ministry of Health in Diyarbakır, Türkiye. Results More than half of the patients were female and had stage 4 cancer. Different types of cancer were detected (breast cancer, cancer of the digestive organs, lymphatic and hematopoietic cancer, cancer of the genital organs, cancer of the respiratory organs, etc.). It can be stated that the average values obtained by patients from patient-centered communication and its sub-dimensions are high. There are positive, moderate and low and significant relationships between the overall patient-centered communication and patient engagement, patient satisfaction, service quality perception and quality of life. It was statistically revealed that patient-centered communication positively affected patient engagement, health-related quality of life, service quality perception, and patient satisfaction . Conclusion Patient-centered communication positively affects various short and medium-term health outcomes and this study offers suggestions for improving patient-provider communication.